Can home care work be organized to promote musculoskeletal health for workers? Study protocol for the Norwegian GoldiCare cluster randomized controlled trial - Fredrik Klæboe Lohne; Marius Steiro Fimland; Andreas Holtermann; Svend Erik Mathiassen; Heike Fischer; Trine Minde Gellein; Skender Redzovic (BMC, 2022)
Abstract Background Home care workers perform physically strenuous tasks, in particular when handling patients with high care demands. Thus, musculoskeletal pain and sick leave is greater in this group than in the general population. To ease these issues, we will implement a Goldilocks Work intervention (GoldiCare), redistributing schedules between workers to achieve a "just right" weekly structure of physical work that can promote health. This protocol paper describes the content, design, implementation and evaluation of the cluster randomized controlled trial of the GoldiCare intervention in home care. Methods The cluster randomized controlled trial is a 16-week workplace organizational intervention implemented through operations managers at the home care units. The operations managers will be introduced to the Goldilocks Work Principle and a GoldiCare tool, to assist the operations managers when composing a "just right" distribution of work schedules throughout the week. The GoldiCare tool provides an overview of the physical strain for each shift, based on the number of patients and their need for care. We expect to include 11 units, which will be randomized to either intervention or control at a 1:1 ratio. Home care workers assigned to the control group will continue to work as normal during the intervention period. Musculoskeletal pain in neck/shoulder and lower back will be the primary outcomes and we will also evaluate the composition of physical behaviors as well as fatigue after work as secondary outcomes. We will collect data using (1) daily questions regarding musculoskeletal pain and fatigue after work, (2) 7 days of objective measurements of physical behavior, (3) questionnaires about the participant's characteristics, health, and workplace psychosocial stressors and (4) information on the implementation of the GoldiCare tool. In addition, a process evaluation will be conducted using focus group discussions and individual interviews. Discussion Due to the increasing aging population in need of care, measures that can improve the health of home care workers are paramount for the sustainability of this sector. This organizational intervention is based on information available nation-wide, and therefore has the potential to be scaled to all municipalities in Norway if proven effective. Trial registration This clinical trial was registered on 08/05/2022 under NCT05487027 .